Performance analysis of phase-change material in battery thermal management with bionic leaf vein structure. (25th June 2022) - Liu, Fen; Wang, Jianfeng; Liu, Yiqun; Wang, Fuqiang; Chen, Yaping; Lu, Yanbing; Liu, Hui; Du, Qian; Sun, Fuzhen; Yang, Na
Highlights: Biomimetic leaf vein fin is used to heat transfer in PCM. PCM is coupled with the cooling wall to achieve better battery cooling. The economical cooling parameters for uniformly stabilizing the cell temperature are derived as φ = 0.4, t w = 26 °C, and d = 4 mm. The cooling efficiency of the proposed system is 29.7%. Abstract: Low thermal conductivity limits the application of phase change material (PCM) in a battery cooling system as a passive thermal management system. Leaf veins are extensively represented as a classical branching structure that absorbs heat in the energy transfer systems of plants. To improve the overall thermal conductivity, this paper proposes a PCM battery thermal management system coupled with a leaf vein fin. First, by comparing different topology parameters, a topological optimization structure using COMSOL simulation is adopted to design a bionic leaf vein fin for heat transfer. Subsequently, we perform a numerical ANSYS simulation for a PCM cooling system coupled with a leaf vein fin based on the heat generation features of a LiFePO4 battery. Consequently, the leaf vein fin coupled with PCM can efficiently remove heat from the cell surface and uniform the cell surface temperature. By comparing battery temperature and PCM melting, the leaf vein fin cooling systems demonstrates a 34.6% increase in temperature drop compared to that of the traditional rectangular fin. Eventually, the economical cooling parameters for uniformly stabilizing the cell temperature in the appropriate operating range are derived as φ = 0.4, t w = 26 °C, and d = 4 mm by comparing different volume fractions, wall temperatures, and fin thicknesses.